Prenatal Diagnosis of Megacyst In Early Pregnancy: A Case Report - Karaşahin, Emre; Gezginç, Kazım; Fidan, Ulaş; Ergün, Ali; Başer, İskender (Gynecology Obstetrics & Reproductive Medicine, 2007)
A case with an incidental ultrasonographic finding of a megacysty in the 14th week of pregnancy, leading to an early diagnosis of Trisomy 18 is presented. An 18-year-old primigravida attending to outpatient clinic for her routine antenatal check up at the 14th week of her pregnancy was observed to have a fetus with a 12 mm bladder. There were no other apperant major organ or system abnormalities. Under the guidance of current literature, the family was counseled by obstetrics and genetics departments, and a chorion villus sampling was adviced. The result of the CVS was reported as Trisomy 18. The family’s wish of termination of the pregnancy was evaluated and the medical abortion with misoprostol induction was achieved. When evaluating and screening an early pregnancy with ultrasound for fetal abnormalities, the size of the fetal bladder should be evaluated carefully and megacystic cases should be kept in mind with the possibility of chromosomal abnormalities.